KEPUASAN KERJA SEBAGAI VARIABEL MEDIATOR ANTARA GAYA KEPEMIMPINAN DAN TURNOVER INTENTION: STUDI KASUS PADA HOTEL DI BOGOR - Siti Komariah; Anggraini Sukmawati; Sadikin Kuswanto (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
Employee turnover could be prevented by identifying the factors causing employee intention to leave the company. This study aimed to analyze the effect of leadership style on the turnover intention with job satisfaction as the mediator. Data were collected through questionnaires distributed to 130 employees in a three-star hotel in Bogor. The sampling method was a census. This study used the descriptive analysis method and Partial Least Square-Structural Equation Model (PLS-SEM) modeling to analyze the influence between variables. The results showed that authentic leadership style has a strong and significant influence on job satisfaction. It was reflected in the leaders who focus on goals, encourage open communication, and have the attitude to supervise and monitor irregularities and take corrective actions. Job satisfaction had a strong and significant influence on employee turnover intentions, reflected on supervision, working situation, recognition and appreciation, and promotion. Authentic leadership style had an insignificantly and weak influence on employee turnover intention. Authentic leadership style significantly influenced turnover intentions through job satisfaction. Keywords: authentic leaderhip, communication, competency, partial least square (PLS-SEM), recognition and appreciation